OPERATOR TRAINING SIMULATOR KALTIM-4 (OTS) DEVELOPMENT WITH AMMONIA SYNTHESIS PROCESS UNIT - DARUNDONO (NIM: 13205111); Pembimbing : Prof. Dr. Ir. Bambang Riyanto Trilaksono, KHRISNA
Operator Training Simulator is a computer network based simulation machine that can be used for operator training program to familiriaze the operator with the plant. The main components of OTS are the simulation server (contains plant models), database server (for recording events), and interaction stations between the operator, training instructor, and the plant models (via Graphical User Interface or GUI). With this system, the training program can be done anytime without disturbing the real plant. By intensifying the training and providing more dangerous situations by the training program, it will give an increase in the operator’s capabilities in handling and operating the plant. In addition, by using a database server the training program is even better because it has the ability to implement a scoring system and also session saving in case the simulation is suddenly stopped, etc. In this final project, the OTS Kaltim-4, which is the OTS for Ammonia Production Unit of PT. Pupuk Kaltim 4, Tbk., will be developed by adding the ammonia synthesis process unit. The models addition will be done by processes, control valves, and controllers modelling, which these three parts will be unified as a control system loop. There will be twenty one loops that will be modelled in this final project. The modelling procedures and simulation will be done using MATLAB R2007a software, while the implementation in the simulation server will be done by using Scilab 4.1.1. The success parameter will be determined by evaluating the value of the best fit, which is a percentage value that describes the vicinity of the model with the real output of the plant. The best fit values of the modelling is ranged between 51.6 to 92.41 %. There are still some models with poor best fit that caused by insufficient data record that acting as the models’ input. GUI development will be done by using Wonderware Intouch and it will be used to make five picture (Ammonia Synthesis 1, Ammonia Synthesis 2, Ammonia Synthesis 3, Ammonia Synthesis 4, and Ammonia Synthesis 5). At the end of this report, there will be an integration between the additional process unit with the existing system, so there will be a brief explanation about Object Linking and Embedding for Process Control (OPC) that interconnects the simulation server with the GUI. By doing this integration process, it will be found that the existing system can interact and be integrated with the additional process unit.